Perception towards practice environment among nurses working in a teaching hospital, Nepal - Khadka, Romi; Sharma, Kalpana (Journal of Chitwan Medical College, 2024)
Background: A healthy nursing practice environment maximizes the health and well-being of nurses, quality patient outcomes, organizational performances and overall societal outcomes. This study aimed to identify the perception among nurses towards practice environment. Method: A cross-sectional descriptive study was carried out among nurses working in different units of Chitwan Medical College Teaching Hospital, Nepal from 19 Dec 2023 to 02 Jan 2024. Probability simple random sampling was used. Ethical approval was obtained. Practice Environment Scale of the Nursing Work Index (PES-NWI) was used to collect the data through self-administered questionnaire. Data were analysed using descriptively for professional and perception toward nurse practice environment. Chi-Square test was used to measure the association. A p-value <0.05 was considered statistically significant. Result: Out of 120 nurse respondents most (97.5%) were 20 years and above, two-third (70%) had completed PCL nursing and were working as staff nurse (74.2%). Median percentage of perception was higher (75.0%) in collegial nurse-physician’s relations followed by nursing foundations for quality of care (73.7%) and lower on staffing and resource adequacy (62.5%). More than two-third (67.5%) perceived favourable nursing practice environment, 23.3% mixed and 9.2% unfavourable nursing practice environment. The level of perception towards nursing practice environment was significantly associated with present working unit (p=0.041). Conclusion: Nurses perception toward practice environment was favourable. Staffing and resource adequacy were the premier concern.